Stomata-targeted nanocarriers enhance plant defense against pathogen colonization - Suppanat Puangpathumanond; Heng Li Chee; Cansu Sevencan; Xin Yang; On Sun Lau; Tedrick Thomas Salim Lew (Nature Communications)
Abstract Plant pathogens significantly threaten food security and agricultural sustainability, with climate change expected to exacerbate outbreaks. Despite these growing threats, current agrochemical delivery remains untargeted and inefficient. In this study, we develop surface ligand-engineered nanoparticles for targeted delivery to stomata (SENDS), a nanocarrier system designed to target stomatal guard cells, which serve as key pathogen entry points into the plant apoplast. Our approach employs rational ligand engineering of porous nanoparticles, optimizing ligand orientation for efficient stomata targeting across different plant species. Foliar application of SENDS encapsulating an antimicrobial plant alkaloid reduces colonization of Xanthomonas campestris, a major crop pathogen, by 20-fold compared to untargeted nanocarriers. Quantitative assessment of stomatal aperture movement and photosynthetic performance confirms that SENDS enhance plant defense against invading pathogens without disrupting natural stomatal function. This nanobiotechnology approach provides a targeted strategy to improve plant disease resistance, offering new insights into nanocarrier design for more resilient and sustainable agriculture.